An Electroanalytical Instrument Equipped with Wireless Communication Network and Graphical User Interface for Real-time Monitoring Wastewater Status from Batik Industry / Mohammad Nizar Mohamed Zukri and Elmi Abu Bakar - Mohamed Zukri, Mohammad Nizar; Abu Bakar, Elmi (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2017)
Effluent discharge from the Batik Industries need to adapt the continuous monitoring system in order to cope with the growing economic. Non-invasive analytical instrument was designed in this work for real-time monitoring of wastewater status from batik factories. Compared with existing instrument, this instrument was simplified with wireless and portable, maximal convenient operator with aided Graphical User Interface, and can be applied for field work such as installing sensor at final discharge point. In this paper, a wireless instrument for determine conductivity, temperature and pH as an indicator for wastewater status was demonstrated and characterized. The synthetic solution was prepared for quality data references, data known and apply correction, robustness and interferences effect. The development of algorithm and mathematical formulation was established in order to obtain the directly measurement method for data acquisition and transmission. To demonstrate the performance of the instrument, the data comparison was made with the Inductive Couple Plasma (ICP-OES) for laboratory control sample. Finally, form the data analysis confirmed this instrument could provide wastewater status in Batik's Effluent in a convenient and non-invasive manner, and simultaneously enhance the awareness of batik entrepreneurs regarding to environmental pollution issues.